Ibuprofen Induces Reduction of the Proliferation-Seeking Radiotracer Tc-(V)DMSA Uptake in Severe Epithelial Breast Hyperplasia without Atypia - Vassilios Papantoniou; Angeliki Tsaroucha; Pipitsa Valsamaki; Spyridon Tsiouris; Evangelia Sotiropoulou; Theodore Karianos; Spyridon Marinopoulos; Athina Fothiadaki; Maria Sotiropoulou; Aikaterini Archontaki; Konstantinos Syrgiannis; Konstantinos Dimitrakakis; et al. (Molecular Imaging)
The purpose of this study was to investigate if ibuprofen intake can influence mammary uptake of the proliferation-seeking radiotracer technetium 99m–pentavalent dimercaptosuccinic acid ( 99m Tc-(V)DMSA) in women with severe epithelial and atypical epithelial breast hyperplasia. Eight patients with histologically confirmed severe epithelial breast hyperplasia with ( n = 4) and without atypia ( n = 4) were submitted prospectively to 99m Tc-(V)DMSA scintimammography before and after a 4-week course of 400 mg ibuprofen daily oral intake. Lesion to background ratios 60 minutes postinjection were calculated and compared ( t -test) before and after ibuprofen administration. Prior to ibuprofen, the patients with severe epithelial hyperplasia displayed a significantly higher 99m Tc-(V)DMSA uptake ratio compared to those with atypical epithelial hyperplasia (2.40 ± 0.32 vs 1.67 ± 0.09, respectively; p = .003). They also exhibited a more substantial percent decline in tracer uptake postibuprofen compared to women with atypical epithelial hyperplasia (62.0 ± 7.1 vs 15.0 ± 0.2, respectively; p = .001). Ibuprofen induces significant uptake reduction of the proliferation-seeking radiotracer 99m Tc-(V)DMSA in severe epithelial breast hyperplasia without atypia. This agent could therefore constitute a potential imaging tool for monitoring chemoprophylaxis effectiveness in women at the early stages of malignant transformation.